PENGARUH WORK-LIFE BALANCE, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT XYZ - Muhammad Nabil Yazid (2023)
This research uses quantitative methods as a way to prove and determine the effect of Work Life Balance, Compensation, Work Environment on Employee Job Satisfaction at PT XYZ. The data collection process used was through a questionnaire with a Likert scale google form to employees of PT XYZ with 37 respondents. The analysis technique used is validity test, reliability test, R-Square, path analysis and hypothesis testing with the help of SmartPLS 4.0. The results of the test obtained (1) Work Life Balance has a positive and significant effect on Employee Satisfaction of PT XYZ (2) Compensation has a positive and significant effect on Employee Satisfaction of PT XYZ (3) Work Environment has a positive and significant effect on Employee Satisfaction of PT XYZ (4) Work Life Balance, Compensation and Work Environment simultaneously have a positive and significant effect on PT XYZ Employee Job Satisfaction. Keywords: Work Life Balance, Compensation, Work Environment and Job Satisfaction.